2017
DOI: 10.1080/20008686.2017.1287986
|View full text |Cite
|
Sign up to set email alerts
|

Modelling human Puumala hantavirus infection in relation to bank vole abundance and masting intensity in the Netherlands

Abstract: This paper deals with modelling the relationship between human Puumala hantavirus (PUUV) infection, the abundance and prevalence of infection of the host (the bank vole), mast, and temperature. These data were used to build and parametrise generalised regression models, and parametrise them using datasets on these factors pertaining to the Netherlands. The performance of the models was assessed by considering their predictive power. Models including mast and monthly temperature performed well, and showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Some authors have proposed statistical models to predict outbreak years in PUUV endemic areas. Most of these models take into account the regional intensity of beech mast [31,32], which is a major factor driving overwintering efficiency and population density of the bank vole. Others consider measurements of rodent density of or even virus prevalence in the reservoir, which requires labour-intensive field- and laboratory work [33] but allows assessment of more direct influences of the probability of virus transmission to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have proposed statistical models to predict outbreak years in PUUV endemic areas. Most of these models take into account the regional intensity of beech mast [31,32], which is a major factor driving overwintering efficiency and population density of the bank vole. Others consider measurements of rodent density of or even virus prevalence in the reservoir, which requires labour-intensive field- and laboratory work [33] but allows assessment of more direct influences of the probability of virus transmission to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Few field studies have experimentally addressed hypotheses to test mechanisms proposed to promote the maintenance, spillover or emergence of hantaviruses harbored by reservoir species within a rodent community within its native ecosystem [ 2 , 3 ]. Longitudinal, descriptive studies of rodent populations have suggested that several ecological factors correlate with the increased prevalence of hantaviruses, such as tree mast seeding [ 4 , 5 , 6 ], lower rodent species diversity [ 2 , 3 ], decreased predator abundance [ 7 , 8 , 9 ], climatic events [ 10 , 11 , 12 , 13 , 14 , 15 ], habitat fragmentation [ 16 ], or land cover classes [ 17 ]. Hence, the following question arises: do these ecological factors similarly influence hantavirus prevalence among their respective rodent communities across diverse ecosystems (e.g., Desert Southwest versus a European forest)?…”
Section: Introductionmentioning
confidence: 99%
“…This system allows us to investigate ecological factors that influence hantavirus prevalence and test whether those factors are species-specific. Experimentally altering habitat effects and/or species diversity directly is problematic in field experiments; we therefore altered the availability of resources to simulate mast seeding in temperate forests, a factor that is generally accepted to increase hantavirus prevalence in rodents in the short term [ 5 , 6 , 19 , 21 , 25 ]. We added resources to specific rodent sampling grids to test the hypothesis that an increase in food resources would alter the rodent community, and then to analyze the effects on the two principal hantavirus reservoir species and the rodent community.…”
Section: Introductionmentioning
confidence: 99%
“…In general, acorn availability increases the length of the breeding season and facilitates winter survival of forest rodents resulting in a higher rodent density in the following spring [9,[19][20][21][22]. As a consequence, in the temperate zone, an increased rodent density has been shown to cause upsurges in Puumala hantavirus disease in humans [23,24]. In addition, several North American studies have suggested that acorns and rodents are good predictors for Lyme-disease risk because rodents are reservoir hosts of B. burgdorferi (s.l.)…”
mentioning
confidence: 99%